Finnish settler colonialism in North America : rethinking Finnish experiences in transnational spaces - Andersson, Rani-Henrik; Lahti, Janne (AHEAD : Advanced Studies in the Humanities and Social Sciences, ISSN 2737-2812, 2022)
Finnish Settler Colonialism in North America reinterprets Finnish experiences in North America by connecting them to the transnational processes of settler colonial conquest, far-settlement, elimination of natives, and capture of terrestrial spaces. Rather than merely exploring whether the idea of Finns as a different kind of immigrant is a myth, this book challenges it in many ways. It offers an analysis of the ways in which this myth manifests itself, why it has been upheld to this day, and most importantly how it contributes to settler colonialism in North America and beyond. The authors in this volume apply multidisciplinary perspectives in revealing the various levels of Finnish involvement in settler colonialism. In their chapters, authors seek to understand the experiences and representations of Finns in North American spatial projects, in territorial expansion and integration, and visions of power. They do so by analyzing how Finns reinvented their identities and acted as settlers, participated in the production of settler colonial narratives, as well as benefitted and took advantage of settler colonial structures. Finnish Settler Colonialism in North America examines the diversity of roles, experiences, and narrations of and by Finns in the histories of North America by employing the settler colonial analytical framework.
Keywords: rasismi; monikulttuurisuus; ylirajaisuus; suomalaisuus; kolonialismi; valkoihoiset; POC-ihmiset; kansallinen identiteetti; maahanmuuttajat; uudisasukkaat; amerikansuomalaiset; siirtokunnat; alkuperäiskansat; etniset vähemmistöt; historia; rasism; mångkulturalism; transnationalism; finskhet; kolonialism; vithyade; nationell identitet; invandrare; nybyggare; amerikafinländare; kolonier (gemenskaper); urbefolkningar; etniska minoriteter; personer av färg; Pohjois-Amerikka; Yhdysvallat; Nordamerika; Förenta staterna